2009
DOI: 10.1016/j.jacc.2008.11.044
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Anger and Hostility With Future Coronary Heart Disease

Abstract: The current review suggests that anger and hostility are associated with CHD outcomes both in healthy and CHD populations. Besides conventional physical and pharmacological interventions, this supports the use of psychological management focusing on anger and hostility in the prevention and treatment of CHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
422
6
33

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 652 publications
(481 citation statements)
references
References 81 publications
20
422
6
33
Order By: Relevance
“…However, mental stressinduced myocardial ischemia is known to be unrelated to severity of coronary obstruction or previous revascularization, and can occur in the setting of a negative exercise-or adenosinestress test. 3 We are unable to explain why mental stress-induced myocardial ischemia shows a robust relationship only with state/trait anger, and not with anger expression, but our results are consistent with a recent meta-analysis, 6 where an association with CHD was found for trait anger but not for anger-expression. Another limitation is the lack of CHD outcome data.…”
Section: Discussionsupporting
confidence: 64%
“…However, mental stressinduced myocardial ischemia is known to be unrelated to severity of coronary obstruction or previous revascularization, and can occur in the setting of a negative exercise-or adenosinestress test. 3 We are unable to explain why mental stress-induced myocardial ischemia shows a robust relationship only with state/trait anger, and not with anger expression, but our results are consistent with a recent meta-analysis, 6 where an association with CHD was found for trait anger but not for anger-expression. Another limitation is the lack of CHD outcome data.…”
Section: Discussionsupporting
confidence: 64%
“…Consistent with this interpretation, greater implicit bias has been linked to greater distress during interracial interactions (Mendes et al, 2007), and stress is a known risk factor for cardiovascular disease (Black and Garbutt, 2002). Additionally, high implicit bias that is activated in interracial interactions may contribute to anger and hostility, and feelings of anger and hostility have been linked to poorer circulatory health (Chida and Steptoe, 2009). In contrast, as Whites are a numerical majority, they may be able to construct social spheres that avoid interracial interactions with minorities, should they desire to.…”
Section: Discussionmentioning
confidence: 94%
“…Specifically, psychological phenomena frequently differ across majority-minority group boundaries (e.g., Hehman et al, 2012), and for racial minorities, negative perceptions of the outgroup (e.g., perceived discrimination by the outgroup) have been shown to buffer against race-based stress (Crocker and Major, 1989;Sellers and Shelton, 2003). On the other hand, research has shown that Blacks who harbor negative attitudes towards Whites are more likely to appraise ambiguous events as discriminatory (Johnson and Lecci, 2003), and perceptions of discrimination are related to heightened anger (Meyer and Baker, 2010) -a strong risk factor for circulatory-related diseases (for a meta-analysis, see Chida and Steptoe, 2009). Moreover, discrimination from the outgroup has been linked to anxiety, cardiovascular threat response, hypertension, and mortality among minorities (Barnes et al, 2008;Mendoza-Denton et al, 2002;Pascoe and Richman, 2009;Sawyer et al, 2012;Smart Richman et al, 2010;Williams and Mohammed, 2009).…”
Section: The Link Between Bias and Ingroup Health For Blacksmentioning
confidence: 99%
“…Aggressive behavior and higher levels of anger in experiences of conflict are positively correlated with the development of CVD (15). With a few exceptions, research has not recognized a similar relationship for T2D although T2D is considered a co-morbid condition in patients diagnosed with affective psychoses.. We take the perspective that angry and aggressive behavior puts people in conflict with others and is likely to chronically activate the PSR.…”
Section: Aggressive Behavior and Conflict With Othersmentioning
confidence: 96%